A SYSTEMATIC REVIEW AND META-ANALYSIS ON EFFECT OF LACTOBACILLUS SUPPLEMENTATION ON METHOTREXATE EFFICACY IN RHEUMATOID ARTHRITIS - FAIZAL K., MOHAMMED; K., VARSHA; M., SUVITHA SRI; SHREE, NITHYA; S., RAGUNATH; M., DEEPALAKSHMI (International Journal of Applied Pharmaceutics, 2026)
Rheumatoid arthritis (RA) is a chronic autoimmune disorder characterized by systemic inflammation and joint destruction. Methotrexate (MTX) remains the cornerstone of therapy but is often limited by variable efficacy and adverse effects. Emerging evidence suggests that gut microbiota modulation, particularly through Lactobacillus supplementation, may enhance the efficacy of MTX via the gut–joint axis. To systematically review and analyze the impact of Lactobacillus supplementation on methotrexate efficacy in rheumatoid arthritis, focusing on inflammatory biomarkers and disease activity in both human and animal studies. A comprehensive search was conducted in PubMed, Scopus, Web of Science, and Cochrane CENTRAL up to June 2025 for randomized controlled trials (RCTs) and animal studies comparing MTX+Lactobacillus versus MTX alone. Primary outcomes included TNF-α, IL-6, IL-10, IL-17, CRP, and DAS28. Risk of bias was assessed using Cochrane RoB 2.0 for RCTs and SYRCLE for animal studies. Meta-analysis employed a random-effects model. Human RCTs demonstrated significant reductions in CRP, TNF-α, and IL-6, accompanied by increased IL-10 levels and modest improvement in DAS28 (SMD –0.41). Heterogeneity was attributed to strain, dose, and duration differences. Animal studies provided mechanistic support, showing decreased pro-inflammatory cytokines, enhanced anti-inflammatory markers, and improved histopathology, though findings were not pooled. Gut microbiota-targeted approaches hold promise for improving MTX response, warranting further strain-specific clinical investigations.